Formation of surface states on Pb(111) by Au adsorption - Wei-Chuan Chen; Chin-Hsuan Chen; Angus Huang; Kaweng Lei; David Mikolas; Ming-kwan Dai; Je-Ming Kuo; Dai-Shien Lin; Cheng-Maw Cheng; H.-T. Jeng; S.-J. Tang (Scientific Reports, 2023)
Abstract Using low-energy electron diffraction and angle-resolved photoemission spectroscopy, we investigated the lattice and electronic structures of the Pb(111) surface upon the adsorption of Au atoms at the low temperature T = 40 K. Unlike earlier results showing the formation of PbAu-alloy layers at room temperature, we found that Au atoms form a ultra-thin superstructure, Au/Pb(111)-3 × 3, on top of the Pb(111) surface. Moreover, three surface-state bands, S1, S2, and S3, are induced within and immediately adjacent to the Pb bulk projected band gap centered at the surface zone boundary $${\overline{\text{M}}}_{Pb(111)}$$ M ¯ P b ( 111 ) at the energies of − 0.02, − 1.05, and − 2.56 eV, respectively. First-principles calculation based on Au/Pb(111)-3 × 3 confirms the measured surface-state bands among which the most interesting are the S1 and S3 surface states. They are derived from surface resonances in Pb(111). Moreover, S1, which disperses across Fermi level, exhibits a large anisotropic Rashba splitting with α of 1.0 and 3.54 eVÅ in the two symmetry directions centered at $${\overline{\text{M}}}_{Pb(111)}$$ M ¯ P b ( 111 ) . The corresponding Rashba splitting of S1 bands in Cu/Pb(111)-3 × 3 and Ag/Pb(111)-3 × 3 was calculated for comparison.